2015
DOI: 10.4149/bll_2015_006
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological evaluation of potential impact of β-tricalcium phosphate (HA+ β-TCP) granules on healing of segmental femur bone defect

Abstract: Histopathological evaluation of β-tricalcium phosphate (HA+ β-TCP) granules demonstrated that it has properties to heal segmental femur bone defect in rat. In this study, 27 male white rats were examined. Rats were divided into tree groups. Surgical procedures were done after IP administration of ketamine 5 % and xylazine HCL 2 %. Then an approximately 5-mm long, 3-mm deep and 2-mm wide bone defect was created in the femur of one of the hind limbs using a No. 0.14 round bur. After inducing the surgical wound, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…9,37,38 Studies have confirmed the reliability of rat models for reporting qualitative and quantitative histological assessment of bone healing and regeneration, in both membranous (calvarium) and endochondral (femur) bone defects. 8,23,25,33,34,37,39,40 Although the effectiveness of GBR for treating SBD and the adjunctive role of PDGF have not been studied extensively, based on an earlier in-vivo radiographic study, the present authors reported new bone formation in rat femoral SBD after 2-4 weeks of GBR with alloplastic bone substitute and PDGF. 41 This study envisaged assessment of long term bone healing after GBR of segmental defects along with adjunct PDGF.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…9,37,38 Studies have confirmed the reliability of rat models for reporting qualitative and quantitative histological assessment of bone healing and regeneration, in both membranous (calvarium) and endochondral (femur) bone defects. 8,23,25,33,34,37,39,40 Although the effectiveness of GBR for treating SBD and the adjunctive role of PDGF have not been studied extensively, based on an earlier in-vivo radiographic study, the present authors reported new bone formation in rat femoral SBD after 2-4 weeks of GBR with alloplastic bone substitute and PDGF. 41 This study envisaged assessment of long term bone healing after GBR of segmental defects along with adjunct PDGF.…”
Section: Introductionmentioning
confidence: 83%
“…21,32 Alloplastic beta-TCP has been used an osteoconductive scaffold for regeneration of small to medium bone defects in orthopedic and dental surgery, and are capable of indirect osteoinductivity through entrapment of growth factors and osteoprogenitor cells. 6,11,39,45 Since beta-TCP resorbs faster than osteoconductive allografts and xenografts, it enables early bone formation within the grafted site and mineralization through hastened release of calcium and phosphorus ions. 8,46 The ability of beta-TCP to enhance GBR and peri-implant bone healing have been reported by several experimental studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 40 As previously reported, β-TCP is biodegradable and more easily resorbed than HA. 41 In an ideal situation, it is better that a biodegradable bone substitute is slowly resorbed and replaced by natural bone. 41 In cases that percentage of HA particle was excessive, new bone formation within graft materials might be partly inhibited.…”
Section: Discussionmentioning
confidence: 99%
“… 41 In an ideal situation, it is better that a biodegradable bone substitute is slowly resorbed and replaced by natural bone. 41 In cases that percentage of HA particle was excessive, new bone formation within graft materials might be partly inhibited. 39 40 Therefore, although appropriate BCP ratio was deemed important, it has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%